Macedonian urbanism? Cities, public building, and the character of political space in Macedonia, ca. 350-150 BC - Gallagher, M (2023)
Urbanization has long been recognized as one of main structural developments of Macedonian social life. Despite extensive research into urban development in the lands conquered by Alexander the Great and the old city-state centres of Southern Greece, Macedonia still lacks a systematic study of the phenomenon. In its absence, various views have been advanced that ultimately depend on assumptions about the nature of Macedonian urbanism.